2005
DOI: 10.1099/ijs.0.63511-0
|View full text |Cite
|
Sign up to set email alerts
|

Dinoroseobacter shibae gen. nov., sp. nov., a new aerobic phototrophic bacterium isolated from dinoflagellates

Abstract: A novel group of aerobic anoxygenic phototrophic bacteria was isolated from marine dinoflagellates, and two strains were characterized in detail. Cells were Gram-negative cocci or ovoid rods and were motile by means of a single, polarly inserted flagellum. They were obligate aerobes requiring 1-7 % salinity. The optimal pH range for growth was 6?5-9?0 and the temperature optimum was 33 6C. The bacteria contained bacteriochlorophyll a and spheroidenone as the only carotenoid. The in vivo absorption spectrum dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 32 publications
(22 reference statements)
2
182
0
Order By: Relevance
“…Antibiotic susceptibility tests were performed by the disc diffusion method as described by Shieh et al (2003). Bacteriochlorophyll a content was determined as described by Biebl et al (2005). Other biochemical tests were carried out by using API 20NE and API ZYM strips (bioMérieux) according to the manufacturer's instructions, and by using the Biolog GN2 microplate system according to Ivanova et al (1998).…”
Section: Q Lai and Others 1734mentioning
confidence: 99%
“…Antibiotic susceptibility tests were performed by the disc diffusion method as described by Shieh et al (2003). Bacteriochlorophyll a content was determined as described by Biebl et al (2005). Other biochemical tests were carried out by using API 20NE and API ZYM strips (bioMérieux) according to the manufacturer's instructions, and by using the Biolog GN2 microplate system according to Ivanova et al (1998).…”
Section: Q Lai and Others 1734mentioning
confidence: 99%
“…shibae is a representative of the Roseobacter clade, a large, diverse and ecologically important phylogenetic cluster of Alphaproteobacteria (Wagner-Döbler and Biebl, 2006;Brinkhoff et al, 2008), abundant in temperate and polar marine habitats (Selje et al, 2004;Giebel et al, 2011). It was isolated from the dinoflagellate Prorocentrum lima (Biebl et al, 2005) and lives in symbiosis with marine algae (Wagner-Döbler et al, 2010). Under optimal growth conditions a remarkable variability in cell size and morphology can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…This confirmed that many hypothetical proteins are expressed at detectable levels in the major biofilm organisms, and also indicated that a majority of abundant extracellular proteins are novel. 2 This groundwork has enabled us to examine proteins expressed in biofilms harvested from several neighboring locations, in carefully measured geochemical conditions, using a combination of chromatographic techniques, MS identification and computational analyses/predictions. 3 These methods provide us with a powerful approach to isolate many of the novel proteins along with any known proteins associated with them, and to begin assigning functions using biochemical assays.…”
Section: Novel Proteins From Anmentioning
confidence: 99%
“…First described 15 years ago, the genus Roseobacter has become the core of a group of marine bacteria which are the focus of intense research because of their taxonomic diversity and abundance in the world's oceans as well as their important contribution to the global carbon and sulfur cycles and thus to climate change. Dinoroseobacter shibae is a novel genus within this group that was isolated from toxic marine dinoflagellates 2 and is able to perform aerobic anoxygenic photosynthesis, a way of generating energy using bacteriochlorophyll a which contributes up to 10% to the primary production in the ocean and is presently poorly understood. Dinoroseobacter shibae carries the pufLM genes of the photosynthesis reaction center and has fully functional light harvesting complexes I and II including bacteriochlorophyll a synthesis 4 .…”
Section: A Uniquementioning
confidence: 99%